‘Law and Gospel’ or ‘Gospel and Law’? An attempt to Trans(form) Theologia Viatorum in the Living Church - Ludji, Irene (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This article explores the ordered concepts of ‘Law and Gospel’ by Martin Luther and ‘Gospel and Law’ by Karl Barth. On the one hand, Luther understood Law and the Gospel as two different but not separate concepts of Christian life. The Law is what God asks Christians to do, while the Gospel is what Christians receive from God. On the other hand, Barth believes that theology should focus on the incarnation of Jesus Christ as proclaimed in the Gospel. This article answered two research questions: First, what is the relationship between the approach presented by Luther and Barth? Second, how can these approaches contribute to the attempt to trans(form) theologia viatorum in the living church? This study was conducted by a literature study. The result of the study showed that to transform and form theologia viatorum of the living church, the ability to hold hand in hand (manus in manu) the duty to God (Law), as proposed by Luther, and receiving the good news (Gospel), as suggested by Barth should enable the church to serve the world better.